Short communication: Diversity of tropical plants and their attractant properties for subterranean termite Coptotermes curvignathus - YULIATI INDRAYANI; MUSRIZAL MUIN; TSUYOSHI YOSHIMURA (Biodiversitas Journal of Biological Diversity, 2017)
Indrayani Y, Muin M, Yoshimura T. 2017. Short communication: Diversity of tropical plants and their attractant properties for subterranean termite Coptotermes curvignathus. Biodiversitas 18: 1353-1357. The effectiveness of bio-based attractant from different leaves of tropical plants on subterranean termites Coptotermes curvignathus was examined under laboratory conditions. Five kinds of leaves of tropical plant such as cajuput (Melaleuca leucadendron L.), cinnamon (Cinnamomum burmannii (Nees & Th. Nees) Nees ex Blume, clove (Syzygium aromaticum (L.) Merr. & L.M. Perry), bay (Syzygium polyanthum Wight) and basil (Ocimum sanctum L.) were serving as termite feeding bio-based attractants for C. curvignathus. Bio-based attractants were obtained by cross cut dry leaves into smaller particles (dry weight 200 g) and dipped in 70% ethanol solution for 3 x 24 hrs. The extracts were then subjected to a rotary evaporator at 60 ÂºC until the extract changed to gel condition. 50 workers and five soldiers of C. curvignathus were tested in a no-choice test bioassay to determine their preferred bio-based attractant under the concentration of 10% and 50%. No-choice bioassays chambers were assembled by connecting two clear plastic glasses (bottom diameter 5 cm, top diameter 7 cm) with clear plastic hoses (inner diameter 3 mm, outer diameter 5 mm). Clear plastic hoses connectors allowed termites to move freely between glasses. A laboratory bioassay determined that the response of subterranean termite C. curvignathus on clove leaf was greater than other five leaves as indicated by termite moving time, and did not differ significantly between concentrations. No direct relationships were noted between the speed of the first termite moving time and number of termites recruited to the bio-attractant chamber.